Assessing how bird diversity of urban golf courses is influenced by course and landscape connectivity - Benjamin, Jonathan (Rhodes University, Faculty of Science, Department of Environmental Science)
With increasing urbanisation and corresponding environmental impacts, urban green infrastructure (UGI) and the services it provides are of high importance. However, the degree to which these spaces are beneficial and provide ecological services are influenced by the extent to which patches of UGI are connected to each other. Varying levels of connectivity may enhance or lower the resilience of the UGI and the biodiversity it houses. Although not considered as UGI, golf courses are prominent green spaces in many urban landscapes occupying vast areas of land, and therefore hold potential to aid biodiversity and facilitate species movement. However, the extent which golf courses are able to do so is a function of both the structure and availability of resources on the golf courses, as well as in the surroundings areas or landscape in which they are situated. This notion of connectivity of golf courses to their surroundings UGI (in its many forms) and landscapes has not been adequately explored in the literature as much of the present literature has addressed golf courses' biodiversity in isolation of other UGI, or where it has been considered, only the context in which golf courses were situated has been acknowledged (i.e. urban or rural landscapes). Moreover, as golf courses occupy large areas of lands forms of UGI, they may also be able to enhance the connectivity of the landscapes in which they are situated through increasing land cover, and lowering fragmentation through connecting patches. This however, is also context specific, as seen in natural settings were golf courses would in fact fragment the landscape. This study therefore sought to assess the extent to which urban golf courses are connected to other forms of UGI in the South African context, and illustrate the importance of paying attention to connectivity in an avifaunal diversity study. It also aimed to investigate the potential of urban golf courses to foster avifaunal diversity in comparison to a reference landscape, the direct surrounding urban and residential areas. To analyse the extent to which golf courses in three South African cities were connected to the wider landscape a connectivity analysis was undertaken using GIS software. This analysis indicated that all golf courses were to some extent connected to a range of different UGI. Whilst the level of connectivity fluctuated between golf courses and cities, there was however no significant difference noted. Urban golf courses in the South African context are thus not isolated habitats but connected to other land uses and therefore potentially provide valuable resources that aid biodiversity. Despite being physically connected to surrounding UGI illustrating that both the golf courses benefit from the surrounding UGI and vice versa, at a larger landscape there was not sufficient evidence of the ability of golf courses to enhance connectivity. Although there was little evidence of golf courses' ability to aid connectivity at the larger landscape scale, the observed extent to which golf courses were connected to their directly surrounding landscape and the high presence UGI within the larger landscape, informed the more refined investigation of avian biodiversity of golf courses in comparison to surrounding urban areas in the city of Cape Town. This biodiversity analysis indicated that there was significantly higher bird diversity on golf courses in comparison to the surrounding urban areas. However, the high level of connectivity to directly surrounding UGI that was obtained in the former part of the study proved to have no impact on the diversity noted. In contrast, the connectivity at the landscape scale, a scale addressing the broader landscape, provided valuable insight into factors determining the levels of avifaunal diversity noted. This dissertation therefore provides evidence of the biodiversity supporting function of urban golf courses and highlights the importance of landscape context in ecological assessment. These findings are a starting point for future research about the capacity of golf courses to support biodiversity in conjunction with other UGI. In the Global South context, which is complex and dynamic in nature, this information is vital, as these dynamic and changing landscapes provide opportunities to incorporate, and preserve already existing biodiversity.
Keywords: Birds; Biodiversity; Connectivity; Golf courses -- South Africa; Green space; Urban ecology (Biology)